Spatiotemporal (four-dimensional) modeling and simulation of uranium (238) in Hazar Lake (Turkey) water - Kulahci, Fatih (Springer, 2016)
A spatiotemporal (four-dimensional) model has been proposed for determining the transportation characteristics of U-238. Primarily, three-dimensional distribution of uranium particles is obtained with the point cumulative semivariogram, and then 4D models are obtained with the spatiotemporal point cumulative semivariogram (STPCSV). The U-238 distribution simulation in the lake by means of the STPCSV method provides the similarity levels'', which help to make categorization. Similarity levels are used as equivalence of the radius of influence, which defines the maximum distance that is practically effective in the research field of U-238. Simulation maps also provide a possibility for the U-238 concentration observability in the lake, and hence, radioactive changes can be traced in a very easy way. The radius of influence for U-238 concentrations transportations is carried out for 5 km distance from each station, and an effective simulation is performed for 24 h. The applications of methodologies are achieved for the Hazar Lake, Turkey, which is under excessive groundwater recharge.
Keywords: Uranium; Model; Radionuclide; Cumulative semivariogram; Transport; Characterization; Hazar Lake